Complications of Microsurgery of Vestibular Schwannoma. (28th May 2014) - Betka, Jan; Zvěřina, Eduard; Balogová, Zuzana; Profant, Oliver; Skřivan, Jiří; Kraus, Josef; Lisý, Jiří; Syka, Josef; Chovanec, Martin
Abstract : Background . The aim of this study was to analyze complications of vestibular schwannoma (VS) microsurgery. Material and Methods . A retrospective study was performed in 333 patients with unilateral vestibular schwannoma indicated for surgical treatment between January 1997 and December 2012. Postoperative complications were assessed immediately after VS surgery as well as during outpatient followup. Results . In all 333 patients microsurgical vestibular schwannoma (Koos grade 1: 12, grade 2: 34, grade 3: 62, and grade 4: 225) removal was performed. The main neurological complication was facial nerve dysfunction. The intermediate and poor function (HB III–VI) was observed in 124 cases (45%) immediately after surgery and in 104 cases (33%) on the last followup. We encountered disordered vestibular compensation in 13%, permanent trigeminal nerve dysfunction in 1%, and transient lower cranial nerves (IX–XI) deficit in 6%. Nonneurological complications included CSF leakage in 63% (lateral/medial variant: 99/1%), headache in 9%, and intracerebral hemorrhage in 5%. We did not encounter any case of meningitis. Conclusions . Our study demonstrates that despite the benefits of advanced high-tech equipment, refined microsurgical instruments, and highly developed neuroimaging technologies, there are still various and significant complications associated with vestibular schwannomas microsurgery.